Strategi Guru dalam Menumbuhkan Motivasi Belajar PAI di SMKMiftahul Ulum - Azmi, Tasya Nabila Nur; Hadi, Muhammad Nur; Muhammada, Muhammada; Yusuf, Wiwin Fachrudin (Institut Teknologi Pendidikan Indonesia, 2024)
Motivation to learn is a must for every educator, amid moral degradation it is necessary to improve the quality of students, especially in PAI subjects. The large number of acts of youth violence, rape to narcotics problems need to be addressed so as not to damage the nation's generation, one of which can be done through increasing motivation to study religion. The purpose of this research is to develop a simple, systematic, meaningful Islamic religious education learning model that can be used by teachers as a good learning tool so that it can be used. The approach used in this research is qualitative. This study uses descriptive qualitative research, specifically to describe, explain and verify the phenomenon under study. Data collection techniques used to collect data are observation, interviews, and documentation. Data analysis techniques in this study used data reduction, presentation, and conclusion. Data reduction is sorting by selecting the main things, and focusing on the important things. Data representation is a structured set of information that provides a conclusion and who takes action. Concluding is an effort to draw conclusions continuously carried out by researchers in the field. Based on the results of the study it can be concluded that the motivation for Islamic religious education at SMK Miftahul Ulum Tanjung Arum Sukorejo has increased. We can see this when the method applied by the teacher in learning can make students enthusiastic about participating in learning. For students to be motivated, several things must be done, namely: explaining the objectives, and the benefits of learning, and choosing media, and learning materials that students need. Choose different presentations according to students' abilities and give students lots of opportunities to try and get involved.